The lived experience of foster parents in placing children in care on medication for the management of behaviors associated with fetal alcohol spectrum disorder (FASD) - Richard, Simone (2017)
First Nations children, in the care of Child and Family Services in Manitoba are often placed on medication for the management of behaviours associated with Fetal Alcohol Spectrum Disorder, or its comorbid condition Attention Deficit Hyperactivity Disorder. This study was conducted using a qualitative research design with exploratory qualitative semi-structured interviews to hear the voices of caregiver(s). Semi-structured qualitative interviews were conducted with 15 participants, between January and May of 2017. A qualitative exploratory study was used to analyze the findings, looking for emerging themes in the data. Five thematic concepts emerged; The process for determining the need for medication; the influence of the school system on suggesting the need for medication; the use of medication and other interventions; dependency created by medication and finally; outcomes of children in care with FASD. February 2018